Ancient Jewish prayers and emotions: emotions associated with Jewish prayer in and around the Second Temple period - Egger-Wenzel, Renate; Reif, Stefan C. (Deuterocanonical and cognate literature studies, 2015)
This collection of essays offers an analysis of central texts in Greek, Hebrew and Aramaic relating to emotions within literary prayers. Their discussions touch upon such diverse topics as relations with God, exegesis, education, prophecy, linguistic expression, feminism, happiness, grief, cult, suicide, non-Jews, Hellenism, Qumran and Jerusalem. The articles contribute to a scientific understanding of early Rabbinic and Christian ideas.